Scientific Publication Management Transformation In Disruption Era - Rahardja, Untung; Lutfiani, Ninda; Juniar, Hega Lutfilah (Pandawan, 2019)
New innovations enter the market and create a strong disruption effect, a sign that the era of the decade that is currently happening has experienced many changes in various sectors, including economics, technology, education and politics. This study aims to examine the aspects and direction of the development of research related to the Disruption Age that affects technological developments, one of which is in the field of publication management. The approach used is a study of various definitions and model frameworks that developed around the era of disruption and management of publications as well as mapping and analysis of a number of publications. Judging from the research method, most of the research was carried out through descriptive and conceptual methods in which technological aspects became the focus of research by researchers. Disruption innovation has an impact on publication management, where publication management is increasingly developing with additional technological spices. Management of online-based scientific publications or e-journals that are able to manage scientific publication activities to create better management and publications and improve accessibility. The Ministry of Research, Technology and Higher Education targets 7,000 nationally accredited journals with six ratings. In 2018 there were 20,610 internationally published scientific works in Indonesia. The application of this online-based or e-journal scientific publication management system is able to improve the quality of the process of managing scientific journals to be more systematic and organized to achieve efficiency and improve publications to be global.